Antitumoral potential of carbamidocyclophanes and carbamidocylindrofridin A isolated from the cyanobacterium Cylindrospermum stagnale BEA 0605B. (December 2020) - Pérez, Víctor Tena; Ticona, Luis Apaza; Cabanillas, Alfredo H.; Corral, Santiago Maderuelo; Perles, Josefina; Valencia, Diego Fernando Rosero; Quintana, Antera Martel; Domenech, Montserrat Ortega; Sánchez, Ángel Rumbero
Abstract: Three carbamidocyclophanes, A, F and V, and carbamidocylindrofridin A were isolated from the cultured freshwater cyanobacterium Cylindrospermum stagnale, collected in the Canary Islands. The chemical structures of these compounds were elucidated through NMR, HRMS and ECD spectroscopy. The absolute configuration of carbamidocyclophane A was confirmed using X-ray-diffraction. All compounds showed apoptotic capacity against the SK-MEL-1, SK-MEL-28 and SK-MEL-31 tumour cells. Carbamidocylindrofridin A had the highest anti-tumour potential, with an IC50 of 1 ± 0.3 μ M in the SK-MEL-1 cell line. Graphical abstract: Image 1 Highlights: An unknown carbamidocyclophane and a cylindrofridin were isolated from C. stagnale . Absolute configurations were elucidated by crystal diffraction and ECD. Compounds showed apoptotic capacity against human malignant melanoma cells.